新加坡与马来西亚政治人物言语交际策略对比性分析 = A comparative analysis of the verbal communication strategies used by political leaders in Singapore and Malaysia - 林鼎勋 Lim, Ding Xun (Nanyang Technological University, 2020)
本文主要运用语用学、词汇学及社会语言学的理论分析9位新加坡和11位马来西亚政治人物发表言论时体现的语言特征。本文选取的语料来自两国政治人物针对国内课题（全国大选）、新马外交课题（领空纠纷、水价纠纷）以及国际课题（一带一路计划、美中贸易战）等五项政治课题所发表的公开言论。此次研究的结果显示，两国政治人物的语言特征差异表现为：一、直接与委婉的差异；二、感性与理性的差异。通过比较新加坡与马来西亚的政治及社会发展，本文发现上述差异受言论自由的程度、选民素质、政治文化、地缘政治、外交政策等社会因素所影响。本文希望借此研究让读者对新、马两国的政治语言有更深一层的认识，理解政治人物如何利用语言来达到其政治目的。The study applies pragmatics, lexicology and sociolinguistics theories to the analysis of the linguistic features found in the speeches made by 9 Singaporean and 11 Malaysian political leaders. The speeches made on domestic issues (General Election), diplomatic issues (Airspace Dispute, Water Price Dispute) and international issues (Belt and Road Initiative, US-China Trade War) make up the data used for this study. The results show that the differences in the linguistic strategies used by political leaders of both countries are: 1. The difference between directness and indirectness. 2. The difference between being emotional and rational. By comparing the political and social development of both countries, we conclude that the freedom of speech, the quality of the voters, the political culture, geopolitics and the foreign policies of the countries have an impact on the above differences. Therefore, the study aims to provide readers with a platform to better understand the political language of Singapore and Malaysia, and to know how politicians use language to achieve their objectives through the findings shown in this case study.